2021
DOI: 10.26444/aaem/144416
|View full text |Cite
|
Sign up to set email alerts
|

Level of contamination with deoxynivalenol, zearalenone and fumonisins in cereal products – assessment of consumer exposure

Abstract: Objective. The main aim of this study was to determine the content of mycotoxins, such as: deoxynivalenol (DON), zearalenone (ZEA) and fumonisins (FUM) in cereal products, and such products intended for infants. The secondary objective was to assess consumer exposure to the DON, ZEA and FUM occurring in cereal products, including those intended for infants and young children. Materials and method. The study included cereals and cereal products such as flours, grits, pastas, products of the bakery industry, sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…The LOD obtained was well below the regulated levels for zearalenone in food products and animal feed, which comprise 20-100 ppm. 18,45 But, still, the achieved LOD of 1 µg mL −1 is not enough to compete with highly sensitive analytical tools. Thus, we investigated the opportunity to upgrade the sensitivity of the developed fluorescent sensor system by using the fluorescence enhancement phenomenon with silver nanoparticles that were embedded in the MIP films' structure.…”
Section: Flour Samples Preparationmentioning
confidence: 99%
“…The LOD obtained was well below the regulated levels for zearalenone in food products and animal feed, which comprise 20-100 ppm. 18,45 But, still, the achieved LOD of 1 µg mL −1 is not enough to compete with highly sensitive analytical tools. Thus, we investigated the opportunity to upgrade the sensitivity of the developed fluorescent sensor system by using the fluorescence enhancement phenomenon with silver nanoparticles that were embedded in the MIP films' structure.…”
Section: Flour Samples Preparationmentioning
confidence: 99%
“…Fumonisins are produced by Fusarium verticillioides and Fusarium proliferatum which most frequently attack maize crops worldwide. They can also be found in many other grains such as rice, wheat, barley, rye, and oats (Zentai et al 2019 ; Pokrzywa and Surma 2022 ). Previous research has shown that F. verticillioides produces high levels of mycotoxins in maize and rice-derived foods at an optimal temperature between 25 and 35 °C (Huong et al 2016 ; Sacco et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Na Índia, 84% das 117 amostras de cereais, incluindo trigo, arroz, milho e aveia, testaram positivas para ZEN, sendo que 33% delas ultrapassaram os limites estabelecidos pela UE (Rai et al, 2018). Na Polônia, produtos à base de cereais também apresentaram ZEN, como farinha de milho, com média de 212,0 μg/kg, excedendo o limite de 75,0 μg/kg permitido (Pokrzywa & Surma, 2022).…”
Section: Zearalenonaunclassified